2020
DOI: 10.3390/brainsci10040248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Social Interactions Using the Autism Screening Instrument for Education Planning-3rd Edition (ASIEP-3): Interaction Assessment in Children and Adults with Fragile X Syndrome

Abstract: An efficient and direct measure of social interactions and autism symptoms is needed for fragile X syndrome (FXS) research and clinical care. The Autism Screening Instrument for Educational Planning-Third Edition (ASIEP-3) Interaction assessment is a brief standardized measure that quantifies social responses under different conditions. The feasibility and validity of the ASIEP-3 was evaluated in 26 males and 13 females with FXS, along with cognitive testing and behavior questionnaires. The videos were scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Planning is an important part when going to do an activity. Planning involves a broad series of decisions and explanations of objectives, policies, programs, specific methods and procedures, and program activities (Cordeiro et al, 2020); (Lambrecht et al., 2022). Learning planning is a systematic approach that includes analysing learning needs, formulating learning objectives, developing teaching materials, and evaluating tools to achieve the expected learning objectives (Arora, Fiorino, Pellier, Métivier, & Pesty, 2018); (Hayes et al, 2022).…”
Section: Islamic Religious Education Learning Planning At Smk Thoriqu...mentioning
confidence: 99%
“…Planning is an important part when going to do an activity. Planning involves a broad series of decisions and explanations of objectives, policies, programs, specific methods and procedures, and program activities (Cordeiro et al, 2020); (Lambrecht et al., 2022). Learning planning is a systematic approach that includes analysing learning needs, formulating learning objectives, developing teaching materials, and evaluating tools to achieve the expected learning objectives (Arora, Fiorino, Pellier, Métivier, & Pesty, 2018); (Hayes et al, 2022).…”
Section: Islamic Religious Education Learning Planning At Smk Thoriqu...mentioning
confidence: 99%
“…The ADOS-2′s utility as an outcome measure in FXS research is significantly hindered by its inability to capture change in symptom severity over time. In this pilot study, the authors showed that the ASIEP-3 Interaction Assessment can be reliably administered across a wide range of ages and ability levels among males and females with FXS [ 9 ]. The score profiles correlated well with expected behaviors observed in FXS with ASD revealing a lower percentage of time engaged in interactions and more instances of decreased social responses without significant floor or ceiling effects.…”
mentioning
confidence: 99%
“…Additionally, the ASIEP-3 Interaction Assessment was shown to be patient-friendly with use of toys and objects of interest to each specific patient, as well as a time-efficient measure. Together, results from this study showed that the ASIEP-Interaction Assessment may be a promising and useful measure for the quantification of social interaction skills in individuals with FXS [ 9 ].…”
mentioning
confidence: 99%